2009
DOI: 10.1073/pnas.0807665106
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila cell adhesion molecule Klingon is required for long-term memory formation and is regulated by Notch

Abstract: The ruslan (rus) mutant was previously identified in a behavioral screen for mutants defective in long-lasting memory, which consists of two consolidated memory types, anesthesia-resistant memory, and protein synthesis-dependent long-term memory (LTM). We demonstrate here that rus is a new allele of klingon (klg), which encodes a homophilic cell adhesion molecule. Klg is acutely required for LTM but not anesthesia-resistant memory formation, and Klg expression increases upon LTM induction. LTM formation also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…In flies, a number of cell-adhesion molecules have been shown to affect ethanol responses. The Notchregulated cell-adhesion gene klingon is required for normal olfactory memory (Matsuno, Horiuchi, Tully, & Saitoe, 2009) and for ethanol sedation and tolerance (Berger et al, 2008), whereas the neural cell-adhesion molecule FasII is required for normal acute resistance to ethanol as well as for normal olfactory learning (Cheng et al, 2001). Interestingly, FasII protein levels are reduced in the hangover tolerance mutant (Schwenkert et al, 2008), suggesting that the hangover-encoded transcription factor might directly regulate FasII expression and thereby cell adhesion.…”
Section: Cell Adhesion and Structurementioning
confidence: 97%
“…In flies, a number of cell-adhesion molecules have been shown to affect ethanol responses. The Notchregulated cell-adhesion gene klingon is required for normal olfactory memory (Matsuno, Horiuchi, Tully, & Saitoe, 2009) and for ethanol sedation and tolerance (Berger et al, 2008), whereas the neural cell-adhesion molecule FasII is required for normal acute resistance to ethanol as well as for normal olfactory learning (Cheng et al, 2001). Interestingly, FasII protein levels are reduced in the hangover tolerance mutant (Schwenkert et al, 2008), suggesting that the hangover-encoded transcription factor might directly regulate FasII expression and thereby cell adhesion.…”
Section: Cell Adhesion and Structurementioning
confidence: 97%
“…Notch has also been implicated in the control of sleep (Seugnet et al, 2011;Singh et al, 2011). Finally, Notch activity is required for memory formation in Drosophila and mice (Costa et al, 2003;Ge et al, 2004;Matsuno et al, 2009;Presente et al, 2004). Intriguingly, loss of function of sca disrupts the formation of memories for ethanol reward without disrupting apparent features of the corresponding neuronal circuitry (Kaun et al, 2011).…”
Section: Intracellular Trafficking Pathways Establish Multiple Layersmentioning
confidence: 99%
“…Interestingly, Wrapper appears to be less conserved. Although it is present in all Drosophilidae and the Drosophila genome harbors a Wrapper-related protein, Klingon (Butler et al, 1997;Matsuno et al, 2009), no clear Wrapper orthologs can be identified in mammals. However, there are several GPI-linked Ig-superfamily proteins in the mouse genome whose expression profiles need to be determined.…”
Section: Research Articlementioning
confidence: 99%